Understanding and preventing juvenile delinquency: a qualitative exploration of risk and protective factors among Malaysian adolescents - Syed Mustafa, Sharifah Muzlia; Abdul Aziz, Norazah; Hamzah, Lina Mursyidah; Alias, Nurul Fitriah (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Juvenile delinquency, characterised by unlawful actions committed by individuals under 18, raises considerable societal concerns, necessitating insights into its causes and preventive strategies. This study investigates the leading risk factors associated with delinquency among Malaysian adolescents, employing semi-structured interviews with two probation officers. Thematic analysis revealed family instability, lack of parental support, peer pressure, living environment, education gaps, and delinquents' attitudes as influential factors. The implications extend to understanding, risk identification, and program development for prevention, intervention, and rehabilitation. Furthermore, beyond investigating the causes, this research delves into the intricate dynamics of protective factors influencing Malaysian youth in criminal activities. Drawing from the experiences of the probation officers, the study identified that family, schools, and society at large emerge as pivotal deterrents, playing crucial roles in steering juveniles away from criminal behaviours. This comprehensive exploration aims to deepen our understanding of the multifaceted factors influencing adolescent criminal behaviour, providing valuable insights for the development and enhancement of targeted prevention strategies for juvenile delinquency in Malaysia.